Geospatial Based Coastal Ecotourism Management for Geography Teaching Material Development - Yusoff, Safiah @ Yusmah Muhammad (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Geospatial has been widely and extensively used as a research tool across the human activity spectrum. Education sector is no exemption with geospatial being taught in all education institutions, secondary or tertiary. In geography education, tourism courses are among courses that employ geospatial in their teaching and learning material to define the data collection and associate the data with technology which has geographic and locational component. Coastal ecotourism, for example, utilize geospatial in its management where geographic information can be stored in layers and integrated with geographic software program. The information can then be created, stored, manipulated, analyzed and visualized. More interestingly, the result of the spatial information can be integrate with various other research discipline. This paper reviews: 1) geospatial as one of the tools used in geography teaching material; 2) the application of geospatial in coastal ecotourism management; and 3) geospatial based coastal ecotourism management for geography education. A review from geospatial based coastal ecotourism management for geography teaching material development was established. Hence, its effectiveness and efficiency is also discussed.